Inhibition of Soluble Epoxide Hydrolase Limits Mitochondrial Damage and Preserves Function Following Ischemic Injury - Akhnokh, Maria K.; Yang, Feng Hua; Samokhvalov, Victor; Jamieson, Kristi L.; Cho, Woo Jung; Wagg, Cory; Takawale, Abhijit; Wang, Xiuhua; Lopaschuk, Gary D.; Hammock, Bruce D.; Kassiri, Zamaneh; Seubert, John M. (Frontiers in Pharmacology, 2016)
Aims: Myocardial ischemia can result in marked mitochondrial damage leading to cardiac dysfunction, as such identifying novel mechanisms to limit mitochondrial injury is important. This study investigated the hypothesis that inhibiting soluble epoxide hydrolase (sEH), responsible for converting epoxyeicosatrienoic acids to dihydroxyeicosatrienoic acids protects mitochondrial from injury caused by myocardial infarction. Methods: sEH null and WT littermate mice were subjected to surgical occlusion of the left anterior descending artery or sham operation. A parallel group of WT mice received an sEH inhibitor, trans-4-[4-(3-adamantan-1-y1-ureido)-cyclohexyloxy]-benzoic acid (tAUCB; 10mg/L) or vehicle in the drinking water 4 days prior and 7 days post-MI. Cardiac function was assessed by echocardiography prior- and 7 days post surgery. Heart tissues were dissected into infarct, peri-infarct and non-infarct regions to assess ultrastructure by electron microscopy. Complexes I, II, IV, citrate synthase, PI3K activities and mitochondrial respiration were assessed in non-infarct regions. Isolated working hearts were used to measure the rates of glucose and palmitate oxidation. Results: Echocardiography revealed that tAUCB treatment or sEH deficiency significantly improved systolic and diastolic function post-MI compared to controls. Reduced infarct expansion and less adverse cardiac remodeling were observed in tAUCB-treated and sEH null groups. EM data demonstrated mitochondrial ultrastructure damage occurred in infarct and peri-infarct regions but not in non-infarct regions. Inhibition of sEH resulted in significant improvements in mitochondrial respiration, ATP content, mitochondrial enzymatic activities and restored insulin sensitivity and PI3K activity. Conclusion: Inhibition or genetic deletion of sEH protects against long-term ischemia by preserving cardiac function and maintaining mitochondrial efficiency.